IMPROVING THE QUALITY OF LEARNING MANAGEMENT BY THE HEAD OF MADRASAH ALIYAH NEGERI PULAU TALIABU - Pardin Pardin (INCARE, International Journal of Educational Resources, 2023)
Improving the quality of education in madrasahs is a necessity to maintain the existence of madrasahs as educational institutions that meet the community's needs in terms of human resources in education and religion. This need will be fulfilled if education can initiate the development process of desired cadres. Of course, this phenomenon becomes the responsibility of the madrasah, including all elements from the head of the madrasah to its students. To examine this issue, a study was conducted on madrasah management, madrasah environment, and students at MAN Pulau Taliabu. Data collection techniques used in this research include interviews, observations, and documentation as supporting tools. The results show that the head of the madrasah makes various efforts to improve teaching quality by establishing various quality guidelines: a) providing services commensurate with expectations; b) user complaints as means for continuous evaluation and improvement; c) community development d) implementing common goals through continuous training programs to enhance qualifications for both teachers and students.